2000
DOI: 10.1136/sti.76.6.457
|View full text |Cite
|
Sign up to set email alerts
|

The association between abuse in childhood and STD/HIV risk behaviours in female genitourinary (GU) clinic attendees

Abstract: Objectives:To compare and contrast women with a history of child abuse with those who have no history of child abuse on STI/HIV risk behaviours and safer sex beliefs in an inner city UK sample. Design: Cross sectional sample survey. Methods: Routine female clinic attendees were invited to complete an anonymous self report questionnaire which included background information, sexual and drug risk behaviour, self reported sexually transmitted infections (STIs), psychological distress (Hospital and Anxiety Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…Moreover, violence-prevention and treatment programmes must also pay special attention to female sex workers with abusive histories, as well as those with hazardous alcohol use. Consistent with previous research demonstrating linkages between violent histories and current sexual health problems, including difficulties negotiating safer sex (Petrak, Byrne, and Baker 2000;Mosack et al 2010;Speizer 2010), participants in this study who reported a history of child abuse or witnessing the abuse of their mothers had greater risk of reporting recent IPV. With the recent release of the first US Strategy to Respond to Gender-Based Violence Globally (United States Department of State & United States Agency for International Development 2012), evidence-based programmes such as 'Together for Girls' are examining the role of violent histories on the lives of women (http://www.togetherforgirls.org/).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, violence-prevention and treatment programmes must also pay special attention to female sex workers with abusive histories, as well as those with hazardous alcohol use. Consistent with previous research demonstrating linkages between violent histories and current sexual health problems, including difficulties negotiating safer sex (Petrak, Byrne, and Baker 2000;Mosack et al 2010;Speizer 2010), participants in this study who reported a history of child abuse or witnessing the abuse of their mothers had greater risk of reporting recent IPV. With the recent release of the first US Strategy to Respond to Gender-Based Violence Globally (United States Department of State & United States Agency for International Development 2012), evidence-based programmes such as 'Together for Girls' are examining the role of violent histories on the lives of women (http://www.togetherforgirls.org/).…”
Section: Discussionsupporting
confidence: 86%
“…Sexually abused children are also at risk for STIs related to their abuse, and increased sexual risk behaviours after the sexual abuse 20 21. However, STIs have been found to be related to multiple forms of child maltreatment, not only CSA 20.…”
Section: Discussionmentioning
confidence: 99%
“…In a given year, one in seven children will experience some form of maltreatment,13 including physical, sexual, emotional abuse or neglect. Growing evidence also links exposure to childhood abuse with negative behaviours and problems in adulthood including drug and alcohol use,14–16 obesity,17 mental health problems,18 19 sexual risk taking,20 21 and revictimisation,22 23 along with health conditions such as hypertension, and diabetes,24–27 which may increase risk for PTB 17 28 29…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that women who have been sexually abused in childhood encounter more difficulties negotiating the use of condoms by male partners in an effort to protect themselves (Hillis et al, 2000;Petrak et al, 2000). In New Caledonia, where the margins within which Kanak women can negotiate their sexuality are narrow and where condom use is viewed as a "male business" especially in rural regions and among the less educated (Bougerol & Salomon, 1998), female child sexual abuse appears as an additional burden in regard to decision-making and management of sexuality later on.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, numerous other studies suggest that, alongwith factors linked to a context of both gender inequalities and globally unfavorable social and economic conditions, adult sexual and reproductive health also depends on adverse personal experiences in childhood, especially CSA. Indeed, CSA has been found to be associated with reduced condom use (Maman, Campbell, Sweat, & Gielen, 2000;Molitor, Ruiz, Klausner, & McFarland, 2000), less contraceptive use (Heise, Ellsberg, & Gottmoeller, 2002), unintended pregnancy (Dietz et al, 1999Steel & Herlitz, 2005), abortion (Russo & Denious, 2001;Wingood & DiClemente, 1997) and sexually transmitted infections (STIs) (Hillis, Anda, Felitti, Nordenberg, & Marchbanks, 2000;Petrak, Byrne, & Baker, 2000). Abused women were also found to be at significantly higher risk of experiencing dissatisfaction in their sex lives and of presenting sexual difficulties in adulthood (Loeb et al, 2002;Mullen, Martin, Anderson, Romans, & Herbison, 1996).…”
Section: Introductionmentioning
confidence: 99%